2015
DOI: 10.1536/ihj.15-042
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Graft Size of Modified Blalock-Taussig Shunt for Biventricular Circulation in Neonates and Small Infants

Abstract: The modified Blalock-Taussig shunt (mBTS) is one of the most important palliative procedures in congenital heart surgery. However, in neonates and small infants, operative mortality and morbidity due to excessive pulmonary blood flow or shunt failure remains high. In this study, a small shunt graft (3.0-mm diameter) was estimated to determine the optimal shunt graft size of BTS as an initial palliation for ultimate biventricular circulation. Eighteen patients weighing an average 3.5 kg who underwent mBTS from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…In the majority of neonates, most stages of cardiac repair are performed between 3 months and 2 years after the primary shunting stage, depending on the primary diagnosis and procedure performed. Although progress has been made in primary total correction and the perioperative management of neonates and children with congenital heart diseases, palliative procedures still play a vital role in high-risk patients with complex cardiac lesions such as hypoplastic left heart syndrome ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of neonates, most stages of cardiac repair are performed between 3 months and 2 years after the primary shunting stage, depending on the primary diagnosis and procedure performed. Although progress has been made in primary total correction and the perioperative management of neonates and children with congenital heart diseases, palliative procedures still play a vital role in high-risk patients with complex cardiac lesions such as hypoplastic left heart syndrome ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…M. Shibata с соавт. предложили индекс трансплантата: соотношение площади поперечного сечения трансплантата и площади поверхности тела [18]. Тромбоз шунта в раннем послеоперационном периоде встречается в 9,4-13,7 % случаев [19].…”
Section: осложненияunclassified
“…Studies using CFD for modeling graft-vessel interactions in mBT have shown that the effect of diameter on flow patterns and shear stress/rate distribution is greater than that of other variables, such as the angle of incidence and the shape of the graft. 63 In that regard, the one factor that surgeons should take into consideration when performing mBT is the diameter that best suits the size of aorta and pulmonary artery in a particular child, 107 and mathematical modeling with computer-assisted dynamics might be considered in assisting this task. 108 Retrospective reports have shown evidence of better short-term survival with an RV-PA shunt compared with an mBT shunt.…”
Section: Clinical Implications and Anesthetic Considerationsmentioning
confidence: 99%